Efficacy of Additional Vitamin D 1000 IU on Diabetic Neuropathy Peripheral for Sleep Quality, Moods, and Daily Activity - Tillandsia Filli Folia Primastuti; Rizaldy Taslim Pinzon; Sugaianto Adisaputro (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2024)
Diabetic neuropathy is one of the most common long-term microvascular complications in diabetes mellitus, in which diabetic neuropathic pain is the most frequent symptom. Diabetic neuropathic pain mostly gets worse at night leading to sleep disturbances. Prolonged pain that does not improve can be stressful and decrease quality of life, symptomatic therapy has not been able to reduce the pain completely. This study aims to investigate the efficacy of additional therapy with 1000 IU of vitamin D on sleep quality, mood, and daily activity in patients with diabetic neuropathy. This study was a randomized controlled trial comparing the experimental group which was given symptomatic therapy and 1000 IU of vitamin D supplementary therapy and the control group which was only given symptomatic therapy, both of them were given 3 months of therapy and the pain impact was checked with the Brief Pain Inventory (BPI). Sampling was conducted in February 2021 using consecutive sampling through a computerized block randomization technique. Data analysis was conducted univariately, and bivariate used Mann-Whitney. Based on the Mann-Whitney test, it was found that the administration of 1000 IU of vitamin D to the experimental group showed a significantly superior improvement in sleep quality (p = 0.004), mood (p = 0.002), and daily activities (p =0.003) in the experimental group compared to the control group after 3 months intervention. Additional therapy of 1000 IU of vitamin D improves sleep quality, mood, and daily activity abilities in patients with diabetic neuropathic pain.